Slit Binding via the Ig1 Domain Is Essential for Midline Repulsion by Drosophila Robo1 but Dispensable for Receptor Expression, Localization, and Regulation in Vivo - Brown, Haley E. (G3 (Bethesda), 2015)
The midline repellant ligand Slit and its Roundabout (Robo) family receptors constitute the major midline repulsive pathway in bilaterians. Slit proteins produced at the midline of the central nervous system (CNS) signal through Robo receptors expressed on axons to prevent them from crossing the midline, and thus regulate connectivity between the two sides of the nervous system. Biochemical structure and interaction studies support a model in which Slit binding to the first immunoglobulin-like (Ig1) domain of Robo receptors activates a repulsive signaling pathway in axonal growth cones. Here, we examine the in vivo functional importance of the Ig1 domain of the Drosophila Robo1 receptor, which controls midline crossing of axons in response to Slit during development of the embryonic CNS. We show that deleting Ig1 from Robo1 disrupts Slit binding in cultured Drosophila cells, and that a Robo1 variant lacking Ig1 (Robo1(∆Ig1)) is unable to promote ectopic midline repulsion in gain-of-function studies in the Drosophila embryonic CNS. We show that the Ig1 domain is not required for proper expression, axonal localization, or Commissureless (Comm)-dependent regulation of Robo1 in vivo, and we use a genetic rescue assay to show that Robo1(∆Ig1) is unable to substitute for full-length Robo1 to properly regulate midline crossing of axons. These results establish a direct link between in vitro biochemical studies of Slit–Robo interactions and in vivo genetic studies of Slit-Robo signaling during midline axon guidance, and distinguish Slit-dependent from Slit-independent aspects of Robo1 expression, regulation, and activity during embryonic development.